Status da pesquisa, maturação de frutos e sementes de Physalis peruviana L. - Ferreira, Bianca Sabina Olmedo Monteiro (Universidade Federal de São Carlos, 2024)
Physalis is a fruit of high commercial interest from Latin America, but still with low production in Brazil, mainly imported from Colombia. Regarding national production, there are still few studies on this species, especially those based on crop science aspects within agroecological principles. Therefore, this research aims to carry out a bibliometric analysis on Physalis sp. to evaluate the quality of seeds, post-harvest, and sensory characteristics of Physalis peruviana L. fruits during maturation. For bibliometric analysis, a search was carried out on the Web of Science only using the word “Physalis”, and the publications were classified into different categories considering six species of physalis, P. peruviana, P . angulata, P. alkekengi, P. ixocarpa, P. minima and P. pubescens. For the seed quality and post-harvest experiments, the fruits were harvested at five harvest points, taking into account the morphological marker calyx color: green, yellow-green, yellow, straw-yellow and straw. After extraction, the seeds from each treatment were evaluated for their physiological potential and health quality. To evaluate the fruits, length and diameter, mass, color, pH, total soluble solids, total titratable acidity, mass loss and firmness were evaluated. Studies on physalis indexed in the Web of Science have increased in recent years, with Phytochemistry and Journal of Natural Products being the most relevant journals. The publications have been carried out by researchers from different countries, with emphasis on the United States, China, Brazil, Mexico and Colombia, with the Universidad Nacional de Colombia being the institution with the largest number of publications. P. peruviana was the most researched species in agronomy and food technology. For seed evaluation, the highest seedling emergence and emergence speed were verified in the yellow calyx point. During germination, the points with the highest value were straw-yellow and yellow calyx. The best physalis harvesting point for seed production is with the yellow calyx. In the fruits analysis, the highest value of masses, diameter, height, total soluble solids content and Maturation Index were observed in the most ripe harvest points, and the highest total titratable acidity content and loss of mass in the least ripe points. Fruits harvested with straw calyx tend to lose mass after a period of storage. Therefore, by the quality parameters and ability to maintain characteristics, the ideal harvest point for greater post-harvest use and product durability is the one with a straw-yellow calyx.
Research status, maturation of fruits and seeds of Physalis peruviana L.
Keywords: Fisális; Análise bibliométrica; Germinação; Vigor; Pós-colheita; Qualidade; Orgânico; Goldenberry; Bibliometric analysis; Germination; Post-harvest; Quality; Organic; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::AVALIACAO E CONTROLE DE QUALIDADE DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::FISIOLOGIA POS-COLHEITA; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS